Changes in Oxygen Uptake in Mullet, Liza parsia (Hamilton-Buchanan) Exposed to Dichlorvos - B.C., Mohapatra; A., Noble (Fishery Technology, 2025)
For acute study on oxygen consumption Liza parsia were exposed 96 h to 0.482 ppm of organophosphate insecticide, Dichlorvos 76% (96 h LC so value) and for sublethal effects o I/S, 1/10 and 1/15th of it for 15, 30 and 45 days. Initially the consumption of oxygen ncreased. But it was followed by decrease in acute experiment. In sub-lethal exposures he oxygen consumption remained high without decrease. However, the increase was higher in lower concentrations. ’l11e experiments were conducted ln a brackishwater medium of salinity 10.0Â Â±Â 1.0%Â°, temperature 27.5Â Â±Â 1.5 Â°C and pH 6.0Â Â±Â 0.5.